Electromagnetic Wave Absorbing Composites with a Square Patterned Conducting Polymer Layer for Wideband Characteristics - Won-Jun Lee; Chun-Gon Kim (Shock and Vibration)
The applications of electromagnetic- (EM-) wave-absorbers are being expanded for commercial and military purposes. For military applications in particular, EM-wave-absorbers (EMWAs) could minimize Radar Cross Section (RCS) of structures, which could reduce the possibility of detection by radar. In this study, EMWA composite structure containing a square periodic patterned layer is presented. It was found that control of the pattern geometry and surface resistance induced EMWA characteristics which can create multiresonance for wideband absorption in composite structures.